Image-Based Textbook About ASEAN Countries with the Integration of Qr-Code Technology in Social Science Content - Tuti Arbatia; Wahjoedi; Sugeng Utaya (Universitas Pendidikan Ganesha, 2023)
The need for textbooks used in schools is one of the causes of learning difficulties among students. This development research aims to create picture-based textbooks about ASEAN countries with the integration of QR-Code technology in social studies content for sixth-grade elementary school students. This research and development uses the Dick & Carey development model. Research subjects are design experts, material experts, teachers, and students. Data collection method using questionnaires. The data analysis technique uses quantitative and qualitative descriptive analysis techniques. The design and material expert validation test results are in the valid category. The practicality test showed very practical results, and the attractiveness test obtained a very attractive product. The development results are included in the effective criteria because student learning outcomes increased from the pretest to an increase during the posttest. Thus, learning using picture-based textbooks about ASEAN countries with QR-Code integration is more effective and improves student learning outcomes compared to not using textbooks. The research conclusions show that picture-based textbooks about ASEAN countries with QR-Code integration for class VI elementary schools are feasible and valid for learning. This research implies that teachers can use picture-based textbooks about ASEAN countries with QR-Code integration to support social studies learning for class VI elementary schools.